1995
DOI: 10.1074/jbc.270.28.16660
|View full text |Cite
|
Sign up to set email alerts
|

The Exchange of Arg-Gly-Asp (RGD) and Arg-Tyr-Asp (RYD) Binding Sequences in a Recombinant Murine Fab Fragment Specific for the Integrin αIIbβ3 Does Not Alter Integrin Recognition

Abstract: The murine monoclonal antibody OPG2 is an excellent paradigm of natural RGD ligands and binds specifically to alpha IIb beta 3 integrin. A reactive Arg103-Tyr104-Asp105 (RYD) tripeptide is located in an extended loop, the third complementarity-determining region of the heavy chain (H3). When compared to other RGD ligands, the RYD tripeptide of OPG2 is unique, in that the side chains are fixed in a stable orientation that we have defined by x-ray crystallography. In this study, we express OPG2 H chain segments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…This disintegrin has an IC 50 value for inhibition of platelet aggregation similar to that observed for RGD-containing disintegrins (14). In another example, using a murine Fab fragment specific for the integrin ␣ IIb ␤ 3 , Kunicki and colleagues (40) demonstrated that the cognate RGD sequence could be exchanged with RYD without an alteration in integrin recognition. These data suggest that some limited diversity in this sequence region may be tolerated and still give rise to a ligand with reasonable potency for inhibiting aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…This disintegrin has an IC 50 value for inhibition of platelet aggregation similar to that observed for RGD-containing disintegrins (14). In another example, using a murine Fab fragment specific for the integrin ␣ IIb ␤ 3 , Kunicki and colleagues (40) demonstrated that the cognate RGD sequence could be exchanged with RYD without an alteration in integrin recognition. These data suggest that some limited diversity in this sequence region may be tolerated and still give rise to a ligand with reasonable potency for inhibiting aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…AP7 and PAC1.1 Fd and chain cDNAs were prepared as described previously (6,7). An additional AP7 Fd construct was generated in which the oligonucleotide sequence (CATCAC) 3 was inserted just upstream of the TGA stop codon.…”
Section: Synthesis Of Recombinant Opg2 Fd and Chain Cdna-the Termmentioning
confidence: 99%
“…1 (AP7.1, AP7.2, and AP7.3) were generated by splice overlap extension polymerase chain reaction (7). AP7 Fd cDNA (7) was used as a template to generate AP7.1, AP7.2, and AP7.3 Fd cDNAs.…”
Section: Synthesis Of Recombinant Opg2 Fd and Chain Cdna-the Termmentioning
confidence: 99%
See 2 more Smart Citations